Serum leptin and 25 Hydroxyvitamin D levels in patients with type II diabetes mellitus - Mustafa, Thana I; Saleh, Basil O; Thaker, Abid A (Journal of the Faculty of Medicine Baghdad, 2017)
Background: Vitamin D and Leptin appears to play a range of roles in beta cell growth and insulin secretion and most importantly interaction with other hormonal mediators and regulators of energy and metabolism. Objective: The aim of this study was to measure serum leptin and vitamin D levels and to investigate their relationships with vitamin D and other clinical laboratory parameters in patients with type II diabetes. Subjects and Methods: Blood samples were taken from 80 patients with type II diabetes mellitus encountered during their attending the Internal Medicine clinic consultancy in Ramadi Teaching Hospital and the National Diabetes Center for Treatment and Research at Al-Mustansiriya University and 60 healthy subject. From December 2014 to November 2015. Investigations included serum Leptin, 25OHD, Insulin, HbA1c using ELISA and biochemical test.Results: The median concentration of serum 25 OH vitamin D of patients (15.70 ng/ ml) was significantly lower than healthy controls (20.27 ng/ ml). The rate of vitamin D deficiency (VDD) was significantly higher in patients (82.5%) than healthy controls (48.3%). The serum insulin and HOMA-IR were significant increase in patients had vitamin D < 20 ng/ml when compared with an insufficient/normal group. There were no significant differences in leptin levels between type II DM and healthy control. Conclusion: These results strongly support the role of vitamin D deficiency and serum leptin in pathogenesis of type II diabetes.